Bioconjugated fluorescent organic nanoparticles targeting EGFR-overexpressing cancer cells. Issue 45 (14th November 2017) - Faucon, Adrien; Benhelli-Mokrani, Houda; Fleury, Fabrice; Dutertre, Stéphanie; Tramier, Marc; Boucard, Joanna; Lartigue, Lénaïc; Nedellec, Steven; Hulin, Philippe; Ishow, Eléna
Abstract : EGF-bioconjugated fluorescent organic nanoparticles serve as bright labels to diagnose EGFR-overexpressing breast cancer cells. Abstract : The field of optical bioimaging has considerably flourished with the advent of sophisticated microscopy techniques and ultra-bright fluorescent tools. Fluorescent organic nanoparticles (FONs) have thus recently appeared as very attractive labels for their high payload, absence of cytotoxicity and eventual biodegradation. Nevertheless, their bioconjugation to target specific receptors with high imaging contrast is scarcely performed. Moreover, assessing the reality of bioconjugation represents high challenges given the sub-nanomolar concentrations resulting from the commonly adopted nanoprecipitation fabrication process. Here, we describe how the combination of a magnetic shell allows us to easily generate red-emitting FONs conjugated with the epidermal growth factor ligand (EGF), a small protein promoting cancer cell proliferation by activating the EGF receptor (EGFR) pathway. Dual color fluorescence correlation spectroscopy combined with immunofluorescence is originally harnessed in its time trace mode to unambiguously demonstrate covalent attachment between the FON and EGF at sub-nanomolar concentrations. Strong asymmetric clustering of EGF-conjugated FONs is observed at the membrane of MDA-MB-468 human breast cancer cells overexpressing EGF receptors using super-resolution fluorescence microscopy. Such high recruitment of EGF-conjugated FONs is attributed to their EGF multivalency (4.7 EGF per FON) which enables efficient EGFR activation and subsequent phosphorylation. The large hydrodynamic diameter ( D H ∼ 301 nm) of EGF-conjugated FONs prevents immediate engulfment of the sequestered receptors, which provides very bright and localized spots in less than 30 minutes. The reported bioconjugated nanoassemblies could thus serve as ultra-bright probes of breast cancer cells with EGFR-overexpression that is often associated with poor prognosis.